Blood cell motions and interactions in microchannels - Lima, R. (2010)
Detailed knowledge on the motions and interactions of individual blood cells flowing in microchannels is essential to provide a better understanding on the blood rheological properties and disorders in microvessels. This paper presents the ability of a confocal micro-PTV system to track red blood cells (RBCs) through a 100 μm circular glass microchannel. The technique consists of a spinning disk confocal microscope, high speed camera and a diode-pumped solid state (DPSS) laser combined with a single particle tracking (SPT) software (MtrackJ). Detailed measurements on the motions of RBCs were measured at different haematocrits (Hct). Our results show clearly that this technique can provide detailed information about microscale disturbance effects caused by the blood cells.